Pengelompokan Kabupaten/Kota Di Provinsi Papua Tahun 2023 Berdasarkan Kualitas Sumber Daya Manusia - Sari, Novalianisa Permata; Renaldi, Egi (Seminar Nasional Official Statistics, 2024)
Since the establishment of the Golden Indonesia Vision in 2045, the government has targeted accelerating the distribution of education and improving the level of health and quality of life of the community as one of the efforts to develop the quality of human resources. This research focuses on the grouping of regencies in Papua Province in 2023 based on a composite index that describes the quality of human resources in Papua Province in 2023. The data used in this research is macro secondary data which is analyzed using descriptive analysis in the form of radar charts and inferential analysis using factor analysis. Formation of a composite index using factor analysis. Three factors were obtained which were used to create a composite index which was then used to present a better picture of various indicators supporting human resource development such as education, health, employment, economic and other variables. Then grouping by dividing into five groups based on quantiles to see spatial stratification.